Pengaruh Beban Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan PT XYZ - Nurul Aulia Pratama; Rycha Kuwara Sari; Ferawaty Puspitorini (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research aims to determine whether there is a significant influence between workload and work discipline on the performance employees of PT XYZ. The method used in this research is a quantitative method. The sampling technique used in this research is saturated sampling or the entire population is sampled. The population in this study was 60 respondents. Data analysis using Smart-PLS4 software and hypothesis testing, namely the t test (partial test). Based on the results of the path coefficient hypothesis test, there is a p-value of 0.000 or <0.05 and the t¬-statistics value of workload has a value of 4,063 or > 1.96, so it can be stated that there is a significant influence between workload variables on employee performance. Based on the results of the path coefficient hypothesis test, there is a p-value of 0.000 or <0.05 and the t-statistics value of work discipline has a value of 5,248 or >1.96, so it can be stated that there is a significant influence between work discipline variables on employee performance.